Anti-corrosion coating and preparation method thereof, anti-corrosion coating and application thereof, and anti-corrosion aluminum foil

By coating a fluoride-containing or aluminum-containing anticorrosion coating on the surface of the aluminum foil, the corrosion problem of aluminum foil in lithium-ion batteries is solved, and effective anticorrosion effect is achieved, extending the service life of the battery and improving safety and stability.

CN119735978APending Publication Date: 2025-04-01SHANGHAI QIYUAN EXPLORATION MATERIALS TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411929812.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, aluminum foil is prone to corrosion in lithium-ion batteries, resulting in a decline in battery performance, and the traditional anti-corrosion method is complex in process, high in cost, or has adverse effects on battery performance.

Method used

A preservative coating is used, and its components include solvents, binders and preservatives. The concentration of the binder is 5 to 10% by weight, the mass ratio of the preservative and binders is (4 to 9.5): 1. The preservative is fluoride or an aluminum-containing compound. By coating it on the surface of the aluminum foil, a stable protective layer is formed.

Benefits of technology

Effectively protect the aluminum foil from corrosion, extend the service life of the aluminum foil, reduce the risk of gas generation and thermal runaway, improve the safety and stability of the battery, and at the same time, the cost is relatively low, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735978A_ABST
    Figure CN119735978A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and provides an anticorrosive paint and a preparation method thereof, an anticorrosive coating and application, and an anticorrosive aluminum foil. The anticorrosive paint provided by the invention comprises the following components: a solvent, a binder and a preservative, the preservative is fluoride or an aluminum-containing compound, and the aluminum-containing compound comprises one or more of aluminum hydroxide and aluminum salt. The fluoride and the aluminum-containing compound have excellent chemical stability, can form a stable protection layer on the surface of the aluminum foil, reduce side reaction between the aluminum foil and an electrolyte, prolong the service life of the aluminum foil, reduce the risk of gas generation and thermal runaway, and contribute to improving the safety and stability of the battery; moreover, the anticorrosive paint also comprises a binder, so that strong adhesion between the coating and the aluminum foil can be realized, and the coating is ensured not to be easy to peel off or fall off in the battery preparation and working process, thereby ensuring a long-term protection effect; meanwhile, the anticorrosive paint provided by the invention is relatively low in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to an anti-corrosion coating and a preparation method thereof, an anti-corrosion coating and application thereof, and an anti-corrosion aluminum foil. Background Art

[0002] In lithium-ion batteries, aluminum foil is widely used as a current collector. However, aluminum foil is prone to corrosion under the long-term action of electrolyte, resulting in battery performance degradation or even failure. Lithium bis(fluoromethanesulfonyl imide) (LiFSI) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) have excellent high-temperature stability and chemical stability. However, LiFSI and LiTFSI cannot passivate aluminum foil, which easily causes severe corrosion behavior, limiting their application in lithium battery electrolytes.

[0003] Traditional methods for aluminum foil corrosion protection include chemical plating and anodizing. The chemical plating method forms a protective film on the surface of the aluminum foil through chemical reaction; the anodizing method places the aluminum foil as an anode in an electrolyte and forms a dense aluminum oxide film on its surface by applying voltage, thereby improving the corrosion resistance of the aluminum foil. However, both methods have problems such as complex processes, high costs, or adverse effects on battery performance.

[0004] The related art discloses an anti-corrosion coated aluminum foil for lithium batteries, which discloses the specific information of the coating and the coating sequence, wherein the aluminum foil is coated with a MXene layer on both sides, a graphene thin layer is coated on the surface of the MXene layer, an anti-corrosion layer is coated on the surface of the graphene thin layer, a carbon black coating is coated on the surface of the anti-corrosion layer, a flame retardant layer is coated on the surface of the carbon black coating, and the anti-corrosion layer is coated with a dopamine coating. Although this method can effectively protect the aluminum foil from corrosion, the process is too complicated and the cost is too high in practical applications.

[0005] In summary, developing an efficient and cost-controlled anti-corrosion coating for aluminum foil has become an urgent problem to be solved. Summary of the invention

[0006] In view of this, the present invention provides an anti-corrosion coating and a preparation method thereof, an anti-corrosion coating and application thereof, and an anti-corrosion aluminum foil. The anti-corrosion coating provided by the present invention has simple ingredients and low cost, and the anti-corrosion coating prepared by using the anti-corrosion coating can effectively protect the aluminum foil from corrosion.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] An anticorrosive coating, comprising a solvent, a binder and an anticorrosive agent; the concentration of the binder in the anticorrosive coating is 5-10wt%; the mass ratio of the anticorrosive agent to the binder is (4-9.5):1;

[0009] The preservative is a fluoride or an aluminum-containing compound; the aluminum-containing compound includes one or more of aluminum hydroxide and aluminum salt.

[0010] Preferably, the fluoride comprises one or more of alkaline earth metal fluorides, alkali metal fluorides, aluminum fluoride, yttrium fluoride, zirconium fluoride and manganese fluoride;

[0011] The aluminum salt includes one or more of fluoroaluminate, aluminum phosphate and aluminum sulfate.

[0012] Preferably, the alkaline earth metal fluoride includes one or more of calcium fluoride, magnesium fluoride, barium fluoride and strontium fluoride; the alkali metal fluoride includes lithium fluoride;

[0013] The fluoroaluminates include alkali metal fluoroaluminates.

[0014] Preferably, the binder includes one or more of polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, fluorinated rubber, polyurethane and sodium carboxymethyl cellulose.

[0015] Preferably, the solvent is water or a polar organic solvent; the polar organic solvent includes one or more of N-methylpyrrolidone, methylformamide and dimethylacetamide.

[0016] The present invention also provides a method for preparing the anticorrosive coating according to the above scheme, comprising the following steps:

[0017] mixing a binder and a solvent to obtain a binder solution;

[0018] The binder solution and the preservative are mixed to obtain the anti-corrosion coating.

[0019] The present invention also provides an anti-corrosion coating, the composition of the anti-corrosion coating is the anti-corrosion coating described in the above scheme or the anti-corrosion coating prepared by the preparation method described in the above scheme.

[0020] The present invention also provides the application of the anti-corrosion coating described in the above scheme in the anti-corrosion of aluminum foil.

[0021] The present invention also provides an anti-corrosion aluminum foil, comprising an aluminum foil substrate and an anti-corrosion coating arranged on the surface of the aluminum foil substrate, wherein the anti-corrosion coating is the anti-corrosion coating described in the above scheme.

[0022] The present invention also provides the use of the anti-corrosion aluminum foil described in the above scheme in lithium batteries.

[0023] The present invention provides an anticorrosive coating, the components of which include a solvent, a binder and a preservative; the concentration of the binder in the anticorrosive coating is 5 to 10 wt%; the mass ratio of the preservative to the binder is (4 to 9.5):1; the preservative is a fluoride or an aluminum-containing compound; the aluminum-containing compound includes one or more of aluminum hydroxide and an aluminum salt. The present invention uses fluorides and aluminum-containing compounds as preservatives, which have excellent chemical stability, can form a stable protective layer on the surface of aluminum foil, reduce the side reaction between the aluminum foil and the electrolyte, extend the service life of the aluminum foil, and can also reduce the risk of gas generation and thermal runaway, which helps to improve the safety and stability of the battery; and the anticorrosive coating of the present invention also includes a binder, which can achieve strong adhesion between the coating and the aluminum foil, ensuring that the coating is not easy to peel off or fall off during the preparation and operation of the battery, thereby ensuring a long-term protective effect; at the same time, the anticorrosive coating provided by the present invention has a relatively low cost and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The photographs are of the aluminum foil modified with the anti-corrosion coating and the unmodified aluminum foil in Example 1;

[0025] Figure 2 These are photos of the aluminum foil modified with the anti-corrosion coating in Example 1 before and after being bent 5000 times;

[0026] Figure 3 The two-electrode constant potential anodic polarization curves of the aluminum foil modified with the anti-corrosion coating and the unmodified aluminum foil in Example 1;

[0027] Figure 4 The optical microscope photographs of the aluminum foil modified with the anti-corrosion coating and the unmodified aluminum foil before and after constant potential anodic polarization in Example 1;

[0028] Figure 5 The scanning electron microscope photographs of the aluminum foil modified with the anti-corrosion coating and the unmodified aluminum foil before and after constant potential anodic polarization in Example 1;

[0029] Figure 6 The XPS characterization diagram of the aluminum foil modified with the anti-corrosion coating and the unmodified aluminum foil before and after constant potential anodic polarization in Example 1;

[0030] Figure 7 The three-electrode constant potential anodic polarization curves of the aluminum foil modified with the anti-corrosion coating and the unmodified aluminum foil in Example 2;

[0031] Figure 8 The EIS impedance spectra of the aluminum foil modified with the anti-corrosion coating and the unmodified aluminum foil before and after three-electrode constant potential anodic polarization in Example 2. DETAILED DESCRIPTION

[0032] The present invention provides an anticorrosive coating, the components of which include a solvent, a binder and an anticorrosive agent; the concentration of the binder in the anticorrosive coating is 5-10wt%; the mass ratio of the anticorrosive agent to the binder is (4-9.5):1;

[0033] The preservative is a fluoride or an aluminum-containing compound; the aluminum-containing compound includes one or more of aluminum hydroxide and aluminum salt.

[0034] Unless otherwise specified, all raw materials / components used in the present invention are commercially available.

[0035] The anticorrosive coating provided by the present invention includes a solvent. In the present invention, the solvent is preferably water or a polar organic solvent, and the polar organic solvent preferably includes one or more of N-methylpyrrolidone (NMP), methylformamide and dimethylacetamide; in a specific embodiment of the present invention, the solvent is preferably selected according to the type of the binder so as to be able to dissolve the binder.

[0036] The anticorrosive coating provided by the present invention includes a binder. In the present invention, the binder preferably includes one or more of polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride (PVDF), styrene-butadiene rubber, fluorinated rubber, polyurethane and sodium carboxymethyl cellulose (CMC); the concentration of the binder in the anticorrosive coating is preferably 5-10wt%, specifically 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%. The binder can improve the adhesion between the coating and the aluminum foil, ensuring that the coating is not easy to peel off or fall off during the preparation and operation of the battery, thereby ensuring a long-term protective effect.

[0037] The anticorrosive coating provided by the present invention includes an anticorrosive agent. In the present invention, the mass ratio of the anticorrosive agent to the binder is preferably (4-9.5):1, specifically 4:1, 5:1, 8:1, 9:1 or 9.5:1; the fluoride preferably includes one or more of alkaline earth metal fluorides, alkali metal fluorides, aluminum fluoride, yttrium fluoride, zirconium fluoride and manganese fluoride; the alkaline earth metal fluoride preferably includes one or more of calcium fluoride, magnesium fluoride, barium fluoride and strontium fluoride; the alkali metal fluoride preferably includes lithium fluoride; the aluminum salt preferably includes one or more of fluoroaluminates, aluminum phosphate and aluminum sulfate; the fluoroaluminates preferably include alkali metal fluoroaluminates, specifically preferably potassium fluoroaluminate, sodium fluoroaluminate and lithium fluoroaluminate. One or more; when the preservative includes fluoride and aluminum-containing compound at the same time, the mass ratio of the fluoride to the aluminum-containing compound is preferably 3-5:1, specifically 3.5:1 or 4:1; in a specific embodiment of the present invention, the preservative is preferably calcium fluoride and barium fluoride, and the mass ratio of calcium fluoride to barium fluoride is preferably 1:(1-2), more preferably 1:1; or the preservative is preferably strontium fluoride and aluminum fluoride, and the mass ratio of strontium fluoride to aluminum fluoride is preferably (3-5):1, more preferably 4:1; or the preservative is preferably aluminum hydroxide and aluminum fluoride, and the mass ratio of aluminum hydroxide to aluminum fluoride is preferably 3:(6-8), more preferably 3:7.

[0038] In the present invention, the fluoride has good chemical stability, can form a stable protective layer on the surface of the aluminum foil, can effectively resist corrosion in the electrolyte of the lithium battery, reduce the side reaction between the aluminum foil and the electrolyte, and prevent the aluminum foil from being corroded by the fluoride or other components in the electrolyte during the operation of the battery, thereby extending the service life of the aluminum foil; in addition, the fluoride also has good compatibility with the electrolyte, is not easy to cause the decomposition of the electrolyte, maintains the stability of the electrolyte, thereby improving the cycle performance and life of the battery; the relatively low density of the fluoride will not significantly increase the weight of the battery, and is suitable for lithium batteries with high energy density requirements, especially lithium batteries used in portable devices and electric vehicles. Aluminum-containing compounds (one or more of aluminum hydroxide and aluminum salts) also have excellent chemical stability and can form a protective coating on the surface of aluminum foil, effectively isolating the corrosive components in the electrolyte from the aluminum foil body and reducing the risk of corrosion of the aluminum foil. In addition, the aluminum-containing compound coating can also improve the stability of the aluminum foil under high voltage and prevent side reactions during the battery charge and discharge cycle, thereby extending the life of the battery and improving the overall electrochemical performance. The reaction between the aluminum foil and the electrolyte during battery operation will generate by-products, which may lead to an increase in the internal resistance of the battery, and the aluminum-containing compound coating can reduce the occurrence of such side reactions, thereby maintaining stable battery performance. At the same time, the aluminum-containing compound coating can also improve the interface properties between the aluminum foil and the positive electrode material, such as enhancing adhesion and stability, which helps to improve the overall performance and service life of the battery.

[0039] The present invention also provides a method for preparing the anticorrosive coating according to the above scheme, comprising the following steps:

[0040] mixing a binder and a solvent to obtain a binder solution;

[0041] The binder solution and the preservative are mixed to obtain the anti-corrosion coating.

[0042] The present invention has no special requirements for the method of mixing the binder and the solvent, as long as they can be mixed evenly; in a specific embodiment of the present invention, it is preferred that the binder and the solvent are placed in a glass bottle and then stirred thoroughly.

[0043] The present invention has no special requirements on the way of mixing the binder solution and the preservative, as long as they can be mixed evenly; in a specific embodiment of the present invention, it is preferred to first place the preservative in a glass bottle, then add the binder solution, and stir until the preservative is evenly dispersed in the binder solution.

[0044] The present invention also provides an anticorrosive coating, the composition of the anticorrosive coating is the anticorrosive coating described in the above scheme or the anticorrosive coating prepared by the preparation method described in the above scheme, that is, the anticorrosive coating is prepared from the anticorrosive coating described in the above scheme. In the present invention, the thickness of the coating is preferably 5 to 50 μm, specifically 10 μm, 20 μm, 30 μm or 40 μm.

[0045] In the present invention, the preparation method of the anti-corrosion coating preferably includes: applying the anti-corrosion coating and then drying to obtain the anti-corrosion coating; in the present invention, the coating method is preferably scraping; the coating thickness is preferably 5 to 50 μm, specifically 10 μm, 20 μm, 30 μm or 40 μm; the drying is preferably vacuum drying; the drying temperature is preferably 60°C, and the drying time is preferably 12 to 24 hours.

[0046] The present invention also provides an application of the anti-corrosion coating described in the above scheme in the anti-corrosion of aluminum foil; in a specific embodiment of the present invention, the anti-corrosion coating described in the above scheme is preferably coated on the surface of the aluminum foil and then dried to obtain an anti-corrosion coating on the surface of the aluminum foil; the aluminum foil is specifically aluminum foil for lithium batteries.

[0047] The present invention also provides an anti-corrosion aluminum foil, comprising an aluminum foil substrate and an anti-corrosion coating arranged on the surface of the aluminum foil substrate; the anti-corrosion coating is the anti-corrosion coating described in the above scheme.

[0048] The present invention also provides the application of the anti-corrosion aluminum foil described in the above scheme in a lithium battery. The present invention has no special requirements for the application and can adopt methods familiar to those skilled in the art, such as using the anti-corrosion aluminum foil as a current collector of a lithium battery.

[0049] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] (1) Weigh 1 g of PVDF into a glass bottle, add 19 g of NMP, and stir for 4 h until the PVDF is dissolved and evenly dispersed, thereby preparing a PDVF solution.

[0052] (2) Weigh 0.5 g of calcium fluoride and 0.5 g of barium fluoride into a glass bottle, add 4 g of the PVDF solution prepared in step (1), and stir for 12 h until the calcium fluoride and barium fluoride are evenly dispersed in the PVDF solution to obtain an anti-corrosion coating.

[0053] (3) The anti-corrosion coating prepared in step (2) is scraped onto the cleaned aluminum foil surface with a scraping thickness of 30 μm, and dried in a vacuum oven at 60° C. overnight to obtain an aluminum foil modified with an anti-corrosion coating, which is denoted as F-Al.

[0054] Performance Test:

[0055] The electrolyte used is a LiTFSI-based electrolyte, in which the solvents are DMC (dimethyl carbonate), EMC (ethyl methyl carbonate) and EC (ethylene carbonate), the electrolyte is LiTFSI, the mass ratio of DMC, EMC and EC is 1:1:1, and the concentration of LiTFSI is 1 mol / L.

[0056] The F-Al prepared in step (3) was cut into pole pieces with a diameter of 16 mm and compared with unmodified aluminum foil. Figure 1 For photos of aluminum foil with anti-corrosion coating and unmodified aluminum foil, according to Figure 1 It can be seen that a layer of material can be clearly observed on the surface of the modified aluminum foil, which is the anti-corrosion coating.

[0057] The aluminum foil modified with anti-corrosion coating was subjected to a 5000 bending test. The test results are shown in Figure 2 .according to Figure 2 It can be seen that after 5000 bending tests, there is no obvious change on the surface of the aluminum foil modified with the anti-corrosion coating, and the anti-corrosion coating has excellent adhesion and is not easy to fall off.

[0058] The prepared F-Al pole piece was used to assemble a Li / F-Al half-cell, and the Al pole piece without anti-corrosion coating was used to assemble a Li / Al half-cell. A constant potential anodic polarization experiment was carried out with a polarization voltage of 4.2 V and a polarization time of 18000 s. The test curve is shown in Figure 3 .according to Figure 3 It can be seen that the corrosion current of the half-cell (Li / F-Al half-cell) assembled with aluminum foil coated with an anti-corrosion coating decreases rapidly over time and reaches equilibrium, indicating that no corrosion occurs. However, the polarization current of the half-cell (Li / Al) assembled with aluminum foil without an anti-corrosion coating is unstable over time, indicating that corrosion occurs.

[0059] The battery after the constant potential anodic polarization experiment was disassembled, and the surface of the Al pole piece and the F-Al pole piece before and after polarization was observed using an optical microscope. The optical microscope photos are shown in Figure 4 Scanning electron microscopy (SEM) was used to characterize the surface of the Al pole piece and the F-Al pole piece before and after polarization. The SEM photos are shown in Figure 5 X-ray photoelectron spectroscopy (XPS) was used to characterize the surface of the Al pole piece and the F-Al pole piece before and after polarization. The XPS spectra are shown in Figure 6 .according to Figure 4 and Figure 5 It can be seen that the surface of the F-Al pole piece is evenly covered with the anti-corrosion coating after polarization, and no corrosion occurs, while a large number of pitting pits appear on the surface of the Al pole piece without anti-corrosion coating after polarization; Figure 6 It can be seen that the Al pole piece without anti-corrosion coating has Al metal peak after polarization, indicating that corrosion occurs, while the F-Al pole piece with anti-corrosion coating has only Al metal peak before and after polarization. 3+ The peak indicates that no corrosion occurs.

[0060] Example 2

[0061] (1) Weigh 1 g of CMC into a glass bottle, add 19 g of H2O, and stir for 4 h until the CMC is dissolved and evenly dispersed, thereby preparing a CMC aqueous solution.

[0062] (2) Weigh 0.8 g of strontium fluoride and 0.2 g of aluminum fluoride into a glass bottle, add 4 g of the CMC solution prepared in step (1), and stir for 12 h until the strontium fluoride and aluminum fluoride are evenly dispersed in the CMC solution to obtain an anti-corrosion coating.

[0063] (3) The anti-corrosion coating obtained in step (2) is scraped onto the cleaned aluminum foil surface with a scraping thickness of 20 μm, and dried in a vacuum oven at 60° C. overnight to prepare an aluminum foil modified with an anti-corrosion coating, which is denoted as F-Al.

[0064] Performance Test:

[0065] The electrolyte used is a LiTFSI-based electrolyte, in which the solvents are DMC (dimethyl carbonate), EMC (ethyl methyl carbonate) and EC (ethylene carbonate), the electrolyte is LiTFSI, the mass ratio of DMC, EMC and EC is 1:1:1, and the concentration of LiTFSI is 1 mol / L.

[0066] The F-Al and pure aluminum foil prepared in step (3) were cut into 2×1 cm electrodes, and a three-electrode constant potential anodic polarization experiment was performed using lithium foil as the reference electrode, lithium foil as the counter electrode, and F-Al or Al as the working electrode. EIS impedance spectrum tests were performed before and after polarization. The polarization curves are shown in Figure 2. Figure 7 , impedance spectrum see Figure 8 .

[0067] according to Figure 7 It can be seen that the polarization current of pure aluminum foil is extremely unstable. This change indicates that the natural oxide film on the surface of the aluminum foil is damaged, and the internal aluminum is exposed to the electrolyte and continuously loses electrons and is oxidized under the action of high potential, causing a sharp change in the oxidation current, indicating that corrosion has occurred; while the oxidation current of the aluminum foil modified with an anti-corrosion coating decreases with time, and the oxidation current is stable with small fluctuations, indicating that no corrosion has occurred.

[0068] according to Figure 8 It can be seen that the Rct of pure aluminum foil is significantly reduced after polarization, and the corrosion products diffuse from the surface of the Al foil to the electrolyte, resulting in a decrease in the impedance of the passivation film, indicating that the Al foil is corroded; while the aluminum foil modified with an anti-corrosion coating not only significantly reduces the Rct, but also only slightly decreases after polarization. This may be due to the further uniform dispersion of AlF3 during the polarization process, further improving the interface contact.

[0069] Example 3

[0070] (1) Weigh 1 g of PVDF into a glass bottle, add 19 g of NMP, and stir for 4 h until the PVDF is dissolved and evenly dispersed, thereby preparing a PVDF solution.

[0071] (2) Weigh 0.3 g of aluminum hydroxide and 0.7 g of aluminum fluoride into a glass bottle, add 4 g of the PVDF solution prepared in step (1), and stir for 12 h until the aluminum hydroxide and aluminum fluoride are evenly dispersed in the PVDF solution to prepare an anti-corrosion coating slurry.

[0072] (3) The slurry prepared in step (2) is scraped onto the surface of a cleaned aluminum foil with a scraping thickness of 20 μm, and dried in a vacuum oven at 60° C. overnight to prepare an aluminum foil modified with an anti-corrosion coating, which is denoted as F-Al.

[0073] Performance Test:

[0074] The electrolyte used is a LiTFSI-based electrolyte, in which the solvents are DMC (dimethyl carbonate), EMC (ethyl methyl carbonate) and EC (ethylene carbonate), the electrolyte is LiTFSI, the mass ratio of DMC, EMC and EC is 1:1:1, and the concentration of LiTFSI is 1 mol / L.

[0075] The F-Al and pure aluminum foil prepared in step (3) were cut into 2×1 cm electrode pieces, and a three-electrode constant potential anodic polarization experiment was carried out using lithium foil as the reference electrode, lithium foil as the counter electrode, and F-Al or Al as the working electrode. EIS impedance spectrum tests were performed before and after polarization. The results showed that the anti-corrosion effect was similar to that of Example 2.

[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An anticorrosive coating, characterized in that: The components include solvent, binder and preservative; the concentration of the binder in the anticorrosive coating is 5-10wt%; the mass ratio of the preservative to the binder is (4-9.5):1; The preservative is a fluoride or an aluminum-containing compound; the aluminum-containing compound includes one or more of aluminum hydroxide and aluminum salt.

2. The anticorrosive coating according to claim 1, characterized in that: The fluoride includes one or more of alkaline earth metal fluoride, alkali metal fluoride, aluminum fluoride, yttrium fluoride, zirconium fluoride and manganese fluoride; The aluminum salt includes one or more of fluoroaluminate, aluminum phosphate and aluminum sulfate.

3. The anticorrosive coating according to claim 2, characterized in that: The alkaline earth metal fluoride includes one or more of calcium fluoride, magnesium fluoride, barium fluoride and strontium fluoride; the alkali metal fluoride includes lithium fluoride; The fluoroaluminates include alkali metal fluoroaluminates.

4. The anticorrosive coating according to claim 1, characterized in that: The binder includes one or more of polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, fluorinated rubber, polyurethane and sodium carboxymethyl cellulose.

5. The anticorrosive coating according to claim 1, characterized in that: The solvent is water or a polar organic solvent; the polar organic solvent includes one or more of N-methylpyrrolidone, methylformamide and dimethylacetamide.

6. The method for preparing the anticorrosive coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: mixing a binder and a solvent to obtain a binder solution; The binder solution and the preservative are mixed to obtain the anti-corrosion coating.

7. An anti-corrosion coating, characterized in that: The anti-corrosion coating is composed of the anti-corrosion coating described in any one of claims 1 to 5 or the anti-corrosion coating prepared by the preparation method described in claim 6.

8. Use of the anti-corrosion coating according to claim 7 in the anti-corrosion of aluminum foil.

9. An anti-corrosion aluminum foil, characterized in that: It comprises an aluminum foil substrate and an anti-corrosion coating arranged on the surface of the aluminum foil substrate, and the anti-corrosion coating is the anti-corrosion coating according to claim 7.

10. Use of the anti-corrosion aluminum foil according to claim 9 in lithium batteries.

Citation Information

Patent Citations

  • Coating compositions with anticorrosion properties

    CN103237850A

  • Etching agent for aluminium and aluminium alloys

    CN103249870A

  • Metal anti-corrosive treatment agent and application method thereof

    CN108315728A

  • Interface protection structure, preparation method and battery comprising structure

    CN109728249A

  • Safety coating and application thereof, electrode plate and lithium ion battery

    CN118970023A